Experiential learning design : theoretical foundations and effective principles - Beard, Colin (Colin M.) (New York, NY : Routledge, 2022)
"Experiential Learning Design comprehensively demonstrates the key theories and applications for the design of experiential approaches to learning and training. Learning is gradually moving away from management and delivery of content and toward experiences that encourage learners to take greater responsibility for their own progress. This book's empirically sound, multi-disciplinary approach balances technical-rational and artistic-intuitive design elements to accommodate the complex, often fluctuating capacities of human learning. In-depth chapters cover design principles, social and environmental factors in learning, the importance of senses and emotions, and links between body and brain. This bold, unique perspective shift will enrich the work of learning scientists, instructional designers, educational technologists, and beyond"--
Introducing experiential learning design -- Design basics : becoming an architect of experiential learning design -- The holistic experiential learning design model (HELM) : a complex web of interactions -- Experience design : doing-sensing -- Experience design : sensing-feeling -- Experience design : feeling-thinking -- Belonging : social interactions in social spaces -- Belonging : the human connection with the more-than-human world -- Being : the development of the ontological self -- Back to the drawing board.
Keywords: Experiential learning; Active learning; Instructional systems -- Design; EDUCATION / Distance Education & Learning; EDUCATION / Adult & Continuing Education; EDUCATION / Curricula